Bone regeneration after sinonasal mucocele marsupialization: What really happens over time?. (3rd February 2015) - Terranova, Paola; Karligkiotis, Apostolos; Digilio, Elena; Basilico, Francesca; Bernardini, Elena; Pistochini, Andrea; Bignami, Maurizio; Castelnuovo, Paolo
<x xml:space="preserve">Abstract</x> Objective To evaluate the necessity of reconstructing the eroded bony boundaries after mucocele marsupialization when the mucoperiosteum has been spared. Study Design Retrospective review of 308 patients treated for a sinonasal mucocele. Of these, 116 showed areas of bone reabsorption in their preoperative computed tomography (CT) scan. Methods Of 116 patients showing one or more areas of bone reabsorption who underwent marsupialization of the mucocele, whether using a purely endonasal endoscopic approach or a combined approach, the common factor was that the mucoperiosteum of the paranasal sinus had always been spared and the eroded bone had never been reconstructed. After rigorous selection, 12 adult patients were enrolled to undergo a postoperative CT scan in order to verify what had happened to the eroded bone at least 3 years following the surgical marsupialization of the mucocele. Results In 66, 6% of patients, the postoperative CT scan showed complete self‐reconstruction of bone that had previously been eroded by the mucocele. No enophthalmus, meningocele, or other facial deformities were noted in our selection group, despite not having undergone surgical reconstruction of the bone. Conclusions Even taking into account the small number of patients enrolled in the present study, indications are that there is no need to reconstruct the eroded bone, as would appear from our results that sparing the mucoperiosteum is enough to enable the bone to regenerate. Nevertheless, larger scale studies of the subject are merited. Level of Evidence 4. Laryngoscope, 125:1568–1572, 2015